Investigating the Mechanism of Action of Diketopiperazines Inhibitors of the Burkholderia cenocepacia Quorum Sensing Synthase CepI: A Site-Directed Mutagenesis Study - Buroni, Silvia; Scoffone, Viola C.; Fumagalli, Marco; Makarov, Vadim; Cagnone, Maddalena; Trespidi, Gabriele; De Rossi, Edda; Forneris, Federico; Riccardi, Giovanna; Chiarelli, Laurent R. (Frontiers in Pharmacology, 2018)
Quorum sensing (QS) is a bacterial intercellular communication process which controls the production of major virulence factors, such as proteases, siderophores and toxins, as well as biofilm formation. Since the inhibition of this pathway reduces bacterial virulence, QS is considered a valuable candidate drug target, particularly for the treatment of opportunistic infections, such as those caused by Burkholderia cenocepacia in cystic fibrosis patients. Diketopiperazine inhibitors of the acyl homoserine lactone synthase CepI have been recently described. These compounds are able to impair the ability of B. cenocepacia to produce proteases, siderophores, and to form biofilm, being also active in a Caenorhabditis elegans infection model. However, the precise mechanism of action of the compounds, as well as their effect on the cell metabolism, fundamental for candidate drug optimization, are still not completely defined. Here, we performed a proteomic analysis of B. cenocepacia cells treated with one of these inhibitors, and compared it with a cepI deleted strain. Our results demonstrate that the effects of the compound are similar to the deletion of cepI, clearly confirming that these molecules function as inhibitors of the acyl homoserine lactone synthase. Moreover, to deepen our knowledge about the binding mechanisms of the compound to CepI, we exploited previously published in silico structural insights about this enzyme structure and validated different candidate binding pockets on the enzyme surface using site-directed mutagenesis and biochemical analyses. Our experiments identified a region near the predicted S-adenosylmethionine binding site critically involved in interactions with the inhibitor. These results could be useful for future structure-based optimization of these CepI inhibitors.